2020
DOI: 10.1021/acs.inorgchem.0c01663
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Heteroaromatic Antenna on the Binding of Chiral Eu(III) Complexes to Bovine Serum Albumin

Abstract: The cationic enantiopure ( R,R ) and luminescent Eu(III) complex [Eu(b iso Qcd)(H 2 O) 2 ] OTf (with b iso Qcd = N,N′ -bis(2- iso quinolinmethyl)- trans -1,2-diaminocyclohexane N,N′ -diacetate and OTf = triflate) was synthesized and characterized. At physiological pH, the 1:1 [Eu(b iso … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 72 publications
1
20
0
Order By: Relevance
“…It is also the most extensively studied protein due to its importance in physiological and pharmacological functions. It is advantageous to study serum albumin, as the limited number of binding sites with high specificity plays a pivotal role in the transportation and delivery of different endogenous and exogenous species . Bovine serum albumin (BSA), having a 76% sequence homology for human serum albumins (HSA), has been broadly studied, as it is the most abundant model protein of blood plasma. , From literature reports, it has been observed that vanadium complexes showing higher DNA and protein binding ability exhibited better cytotoxicity, and so the assessment of this ability is an important aspect prior to anticancer studies, ,,, but the involvement of several other mechanisms of cellular activity may also be possible. In some reports, the cellular cytotoxicity activity of transition-metal complexes (V and Cu) follows a mechanism of action different from DNA and protein interactions. Possibly, the increased electron density in the aromatic ring systems, aqueous solubility, membrane permeability, or specific hydrophobic interactions in target binding pockets lead to an increase in cytotoxicity. , In this context, due to hydrophobicity, enhancement in the bioavailability of a drug by its internalization to the target cells and ability to reach the site of action is another point of interest. , Thus, in this work, we have sought to correlate the behavior of complexes in aqueous stability, hydrophobicity, DNA/protein interactions related to their cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…It is also the most extensively studied protein due to its importance in physiological and pharmacological functions. It is advantageous to study serum albumin, as the limited number of binding sites with high specificity plays a pivotal role in the transportation and delivery of different endogenous and exogenous species . Bovine serum albumin (BSA), having a 76% sequence homology for human serum albumins (HSA), has been broadly studied, as it is the most abundant model protein of blood plasma. , From literature reports, it has been observed that vanadium complexes showing higher DNA and protein binding ability exhibited better cytotoxicity, and so the assessment of this ability is an important aspect prior to anticancer studies, ,,, but the involvement of several other mechanisms of cellular activity may also be possible. In some reports, the cellular cytotoxicity activity of transition-metal complexes (V and Cu) follows a mechanism of action different from DNA and protein interactions. Possibly, the increased electron density in the aromatic ring systems, aqueous solubility, membrane permeability, or specific hydrophobic interactions in target binding pockets lead to an increase in cytotoxicity. , In this context, due to hydrophobicity, enhancement in the bioavailability of a drug by its internalization to the target cells and ability to reach the site of action is another point of interest. , Thus, in this work, we have sought to correlate the behavior of complexes in aqueous stability, hydrophobicity, DNA/protein interactions related to their cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The non‐radiative decay rate is found to be larger for Tc (9.52 ms −1 ) in comparison to DTBTA (0.69 ms −1 ) and BHHCT (1.45 ms −1 ), which can be attributed to its weak shielding of the Eu centre against the solvent molecules. Consequently, Tc−Eu has shortest τ obs among the three complexes alongside lowest luminescence brightness (indicated by ϵ×φ Ln ); however, the latter can be improved when Tc binds to serum albumin, as reported previously [44–45] . It should be noted that the solvent also affects the photophysical properties including the lifetime, due to potential changes in refractive index, pH, and coordination to the lanthanide ion.…”
Section: Resultsmentioning
confidence: 56%
“…The interaction among bovine serum albumin (BSA) and two DACH‐based Eu(III) complexes was studied by means of several experimental techniques [53] . Interestingly, we demonstrated that the nature of this interaction is strongly affected by the type of the involved heteroaromatic antenna in the Eu(III) complexes.…”
Section: Luminescent Chiral Lanthanide‐based Complexes Containing Tra...mentioning
confidence: 99%
“…In the latter applications, the formation of ternary ML‐analyte species is monitored at fixed conditions (most often physiological pH and ionic medium) and conditional formation constants are determined. A variety of methods have been employed, such as fluorimetry, spectrophotometry, NMR, and calorimetric titrations [52–54] . In some cases, [53] the combination of different techniques and computational methods is necessary to distinguish between different speciation models ( vide infra ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation